Sudamérica hemisférica: la concepción realista que permita configurar una viable integración regional en el actual sistema multipolar (Tema Central) - Pinto Kaliski, Jaime (2023)
South America has undergone multiple integration processes that have succumbed to the political ups and downs of the region’s governments, with only subregional initiatives surviving, such as the CAN or MERCOSUR. But from the Brazilian geopolitical perspective, a distinguishable regional pole must be created in the international system, based on the Brasilia-Buenos Aires axis, the axis of South American power. UNASUR symbolized the most finished process of this perspective, but the lack of regional consensus prevented its deepening, giving way to another failed initiative, PROSUR. The solution to these successive failures is to change the conception of regional integration towards a realistic approach to international relations, adopting the balance of power in the analysis of the international system. This implies the conception of a South American pole intrinsically intertwined with the rest of the American continent, which recognizes the historical and political link with the Americas and with it, the awareness of the importance of the United States for stability in the hemisphere, beyond the American governments of the day. Our contribution from Realism is to propose the concept of “hemispheric South America”, to reflect the real possibilities of regional integration with autonomy from extra-regional powers, based on the Brasilia-Buenos Aires axis, and that at the same time, be recognized as a region anchored to the rest of the continent in terms of its historical and political future, within an increasingly anarchic international system due to its growing multipolarity.